(untitled) (Research, Society and Development, 2022)
Objective: To identify the main chemical constituents and pharmacological activities of Chenopodium ambrosioides L. Methodology: This is an integrative review carried out in the LILACS, SciELO and PubMed electronic databases, using the following descriptors: “Chenopodium ambrosioides”, “Erva-de-Santa-Maria”, “Plantas medicinais” e “Compostos Fitoquímicos” (with respective English translations). Full articles, available in Portuguese and English, published between January 2016 and December 2021 were included. Results: The final sample consisted of 10 articles, published more frequently in 2017. As for the regions of the Chenopodium ambrosioides L. plant analyzed, it is verified Most studies analyzed leaves (n: 07), followed by stem (n: 02), seeds (n: 01) and aerial regions (n: 01). It is possible to verify that Chenopodium ambrosioides L. was involved in studies that proved its anti-inflammatory, antibacterial, antifungal, analgesic, antiparasitic, nematicide, vermifuge and antileishmania. Conclusion: Numerous biological activities have been attributed to Chenopodium ambrosioides L. recently in the analyzed studies. It is a promising plant for the production of herbal medicine, with beneficial health properties, with proven therapeutic effects, however, broader studies are needed in an attempt to discover new ways to use the medicinal herb.